KINERJA BIDAN PEMBINA WILAYAH PUSKESMAS DI KOTA BEKASI - Rajab, Wahyudin (Jurnal Kesehatan, 2013)
Wahyudin Rajab1)1) Poltekkes Kemenkes Jakarta-III Abstract: Performance of Supervisors Midwifve of Public Health Centre Area in Bekasi City. Improvement of health services in the city of Bekasi with minimum standards indicators of service were performed by midwives in 2005 has not been showed optimal results. Research purposes to determine the factors associated with the performance of supervisors midwives in health center area of Bekasi city. This research was conducted with cross-sectional design, with a total sample of 104 supervisors midwive of public health center area in Bekasi. Collecting data in this study conducted using questionnaires. The research was conducted during the month of November 2008 - December 2010. Analasis data in this study using univariate, bivariate with chi-square test and multivariate with logistic regression. The results showed that the proportion of supervisors midwive poorly performing regions as many as 109 (43.4%) and 95 (46.6%) on midwives that perform well. And the existence of a significant relationship variables infrastructures (p = 0.000), incentives (p = 0.000), supervision (p = 0.000), and leadership support (p = 0.000) with a midwife builder performance areas. The most dominant factor that has to do with the performance of supervisors midwive incentives variable region is OR 9.64 (95% CI: 4.33 to 21.44) followed by community support variable OR 2.40 (95% CI: 1 , 26 to 4.54). The based of results advice need for coaching, supervision and provision of adequate incentives in the form of rewards to midwife supervisors region, as well as the need for cooperation with professional organizations and academic intitution. Keywords: performance Abstrak: Kinerja Bidan Pembina Wilayah Puskesmas di Kota Bekasi. Peningkatan pelayanan kesehatan di kota Bekasi dengan indikator Standar Pelayanan Minimal (SPM) yang dilakukan oleh bidan pada tahun 2005 belum memperlihatkan hasil yang optimal. Tujuan penelitian untuk menentukan faktor-faktor yang berhubungan dengan kinerja bidan pembina wilayah puskesmas kota bekasi.  Penelitian ini dilakukan dengan desain cross sectional, dengan jumlah sampel sebanyak 104 orang bidan pembina wilayah puskesmas di Kota Bekasi. Pengumpulan data pada penelitian ini dilakukan menggunakan angket kuesioner. Penelitian dilaksanakan selama bulan November 2008 - Desember 2010. Analasis data pada penelitian ini menggunakan analisis univariat, bivariat dengan uji Chi Square dan multivariat dengan uji regresi logistik. Hasil penelitian menunjukan  bahwa proporsi bidan pembina wilayah yang kurang baik kinerjanya sebanyak 109 (43,4%) dan 95 (46,6%) pada bidan yang kinerjanya baik.  Serta adanya hubungan yang bermakna variabel sarana dan prasarana (p= 0,000), insentif (p= 0,000), supervisi (p= 0,000), dan dukungan pimpinan (p= 0,000)  dengan kinerja bidan pembina wilayah. Faktor yang paling dominan berhubungan dengan kinerja bidan pembina wilayah adalah variabel pemberian insentif  OR 9,64 (95%, CI: 4,33 – 21,44) disusul dengan variabel dukungan masyarakat OR 2,40 (95%, CI: 1,26 – 4,54). Hasil penelitian menyaranakan perlu adanya pembinaan, supervisi dan pemberian insentif yang memadai yang berbentuk reward kepada bidan pembina wilayah, serta perlu adanya kerja sama dengan organisasi profesi dan akademisi Kata Kunci: kinerja